Peningkatan Hasil Belajar Matematika Siswa Melalui Pembelajaran Berdiferensiasi dalam Mewujudkan Merdeka Belajar - Muslimin, Muslimin; Hirza, Bonita; Nery, Rieno Septra; Yuliani, Refi Elfira; Heru, Heru; Supriadi, Agus; Desvitasari, Tria; Khairani, Neneng (Program Studi Pendidikan Matematika, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This research is motivated by the not yet optimal application of differentiated learning where teachers have not accommodated students' learning needs, in the form of learning readiness, learning interest and student learning profile (style). This study aims to improve student learning activities and outcomes. Data collection techniques using instruments: (1) student activity observation sheets, and (2) learning achievement tests. Data were analyzed with descriptive statistical analysis and descriptive analysis. The results showed that: The average percentage of completeness of student learning outcomes in cycle I was 92%, increasing to 96% in cycle II. While the percentage of student learning activities in cycle I reached 90.25%, an increase of 92% in cycle II. From the results of the study it can be concluded that the application of differentiated learning through the Problem Based Learning learning model can optimize student learning activities and outcomes.